THE EFFECT OF COMPETENCE, PROFESSIONALISM, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION AS AN INTERVENING VARIABLE AT NUSANET MEDAN - Yola Mirandha; Bagus Handoko; Aulia Arief Nasution (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study is to examine and analyze the influence of competence, professionalism, and work environment on employee performance, as well as the role of motivation in mediating the influence of competence, professionalism, and work environment on employee performance at Nusanet Medan. This type of research is associative with a quantitative approach, and the sample in this study consists of 100 employees, using path analysis as the analytical technique. The results of this study indicate that competence, professionalism, and work environment each have a positive and significant influence on employee work motivation at Nusanet Medan. Additionally, these three factors also have a positive and significant influence on employee performance. Work motivation itself has a positive and significant influence on employee performance. Furthermore, work motivation significantly mediates the influence of competence, professionalism, and work environment on employee performance at Nusanet Medan.